KETERWAKILAN PEREMPUAN DI DPR-DPRD PILAR UTAMA KEADILAN GENDER DALAM KEBIJAKAN PUBLIK - Nur Rahmadani; Hasniati; Muhammad Najib (Institut Agama Islam (IAIN) Kendari, 2025)
Women’s representation in Indonesia’s legislative institutions is still largely understood in quantitative terms through the 30% quota policy, yet it has not fully translated into substantive representation. Previous studies have left a gap by insufficiently integrating structural, institutional, cultural, and media dimensions in explaining the effectiveness of female legislators. This study aims to examine the extent to which women’s representation in the DPR and DPRD contributes to gender justice, to identify the barriers limiting their strategic roles, and to propose strategies for strengthening their legislative capacity. The research employs a literature review method by analyzing scholarly journals, books, and academic reports, framed within representation theory that distinguishes between symbolic and substantive representation. The findings reveal that although the number of women in parliament has steadily increased since the reform era, their presence often remains symbolic due to political patronage, entrenched patriarchy, media bias, and weak institutional support from political parties. Nonetheless, examples of substantive representation exist, such as women’s crucial involvement in the enactment of the Domestic Violence Law (PKDRT) and the Sexual Violence Law (TPKS). These cases highlight the need for internal party reforms, cross-faction solidarity, gender-sensitive political education, and alternative media utilization to enhance women’s substantive roles. The implication is that women’s representation must not be confined to fulfilling quota requirements but should be directed toward multi-level and multi-sector strategies that ensure inclusive democracy and position gender justice as a foundational pillar of sustainable political development.